FACTORS INFLUENCING BUDGETARY CONTROL AMONG SMES IN THE KLANG VALLEY, MALAYSIA - Shefren, Ahmed Sghayer Ali; Arumugam , Dhamayanthi; Balasingam , Suresh (Electronic Journal of Business and Management, 2021)
Small and Medium Enterprises (SMEs) in the Klang Valley often face challenges surviving the dynamic Malaysian economy. Budgetary control is a key instrument to improve performance, yet many SMEs neglect it. This study investigates the factors influencing budgetary control by reviewing four variables: budgetary participation, firm size, firm ownership, and financial preferences. Using primary data from 200 respondents across 47 companies, the research employed descriptive analysis, Pearson correlation, and multiple regression. The results affirm that budgetary participation, firm size, and firm ownership have a significant relationship with budgetary control. However, financial preferences showed an insignificant relationship. The study suggests that larger sample sizes in future research could provide even deeper insights.